2013
DOI: 10.1097/mbc.0b013e32835e63b7
|View full text |Cite
|
Sign up to set email alerts
|

Blood clotting activation analysis for preoperative differentiation of benign versus malignant ovarian masses

Abstract: Preoperative evaluation of patients presenting with ovarian masses is challenging, partly due to shortcomings with the commonly used marker, CA-125. Ovarian cancer is associated with systemic coagulation activation. Measurement of D-dimer, serum tissue factor (TF), and the coagulation process as a whole are considered candidates for improving discrimination between benign and malignant ovarian masses. We therefore sought to identify possible benefits by analyzing preoperative coagulation status in conjunction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Whole blood was incubated with 10 mg/mL lipopolysaccharide (LPS) or PBS without Ca 2þ and Mg 2þ (4 hours, 37 C), followed by incubation with tissue factor HuMab (10 minutes, room temperature). Thromboelastography (TEG) was performed as described (23). In this system, the LPS-induced decrease in clotting lag time (R) represents a measure for tissue factor activity.…”
Section: Thromboelastographymentioning
confidence: 99%
“…Whole blood was incubated with 10 mg/mL lipopolysaccharide (LPS) or PBS without Ca 2þ and Mg 2þ (4 hours, 37 C), followed by incubation with tissue factor HuMab (10 minutes, room temperature). Thromboelastography (TEG) was performed as described (23). In this system, the LPS-induced decrease in clotting lag time (R) represents a measure for tissue factor activity.…”
Section: Thromboelastographymentioning
confidence: 99%
“…38 Our group and others have shown that increased thrombin production as measured by the thrombin generation assay is associated with malignancy and is a predictive marker for VTE. 25,38,39,40 The thrombin generation assay has not been universally accepted as a biomarker in clinical settings 41,42 however, a recent thrombin generation standardization study showed that the standard thrombin generation assay provides good reproducibility in hypercoagulable plasma. 43 When D-dimer and ETP are combined with the Thrombogyn score, the predictive ability of the Thrombogyn score was enhanced.…”
Section: Discussionmentioning
confidence: 92%
“…D‐dimer has been identified as the strongest prognostic biomarker for VTE in patients with cancer compared with previously tested biomarkers 26 . D‐dimer is frequently raised in ovarian cancer and has been proposed as a diagnostic marker useful in triaging patients; hence, the specificity of D‐dimer as a biomarker for VTE in this population is low 38 . Our group and others have shown that increased thrombin production as measured by the thrombin generation assay is associated with malignancy and is a predictive marker for VTE 25,38,39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative TEG hypercoagulation has also been suggested to reflect the degree of malignancy of ovarian masses (Amirkhosravi et al 2013). Dextran has been suggested to reduce thromboembolism in cancer surgery (Foster et al 2017).…”
Section: Discussionmentioning
confidence: 99%